Innovative Design of Sublimation Printing Machine - M N Masri, A Hamid, M Mohamed, M Mohamad, S A Sobri (International Journal of Advanced Science and Technology, 2020)
The textile and clothing industry shift towards the manufacture of high added value products, Malaysia has the potential to develop industrial and home textiles, functional fabrics and high-value fabrics and clothing. In this paper, the main the focus of the innovative product will discuss on the advantages of the invention over the existing sublimation printing machine. These include utilizing flexible roller paper spindle, external refill ink tank, micronized polyethylene wax added in ink formulation and the infra-red ink drying. The outcome of this innovation in technology needed is a rapid and useful process, increase the productivity of the company, knowledge transfer and sharing, reduce cost operation and less waste. Besides, community and society economic enhancement could be achieved at the same time Keywords: sublimation printing, machine, textile, community.